2013
DOI: 10.1128/aem.00068-13
|View full text |Cite
|
Sign up to set email alerts
|

Mountain Pine Beetles Colonizing Historical and Naïve Host Trees Are Associated with a Bacterial Community Highly Enriched in Genes Contributing to Terpene Metabolism

Abstract: eThe mountain pine beetle, Dendroctonus ponderosae, is a subcortical herbivore native to western North America that can kill healthy conifers by overcoming host tree defenses, which consist largely of high terpene concentrations. The mechanisms by which these beetles contend with toxic compounds are not well understood. Here, we explore a component of the hypothesis that beetle-associated bacterial symbionts contribute to the ability of D. ponderosae to overcome tree defenses by assisting with terpene detoxifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
202
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(203 citation statements)
references
References 55 publications
(49 reference statements)
1
202
0
Order By: Relevance
“…The molecular analysis indicated that the predominant species in the D. armandi bacterial community formed a low complexity group with a different structure after starvation. Low-complexity gut microbial communities have been reported for D. rhizophagus, D. valens and D. ponderosae [31][32][33]. Additionally, as found in all of the D. armandi developmental stages, some taxa were shared among the bacterial communities [12].…”
Section: Bacterial Community Structurementioning
confidence: 90%
“…The molecular analysis indicated that the predominant species in the D. armandi bacterial community formed a low complexity group with a different structure after starvation. Low-complexity gut microbial communities have been reported for D. rhizophagus, D. valens and D. ponderosae [31][32][33]. Additionally, as found in all of the D. armandi developmental stages, some taxa were shared among the bacterial communities [12].…”
Section: Bacterial Community Structurementioning
confidence: 90%
“…Plant allelochemical detoxification has also been implicated in certain insect symbioses, notably bark-feeding beetles and leaf-cutting ants. The gut microbiota of the mountain pine beetle Dendroctonus ponderosae include bacteria of the genera Pseudomonas, Serratia, Rahnella, and Burkholderia that bear genes involved in the degradation of terpenes, the principal defensive compounds of the trees infested by these beetles (Adams et al 2013). The leaf-cutting ant Acromyrmex echinatior maintains, and feeds on, the symbiotic fungus Leucocoprinus gongylophorus in its nest.…”
Section: Symbiosis In Eukaryotic Evolutionmentioning
confidence: 99%
“…A fourth Streptomyces strain, DpondAA-B6 (SDPB6), was isolated from a surface-sterilized adult mountain pine beetle collected from a naturally attacked Pinus contorta tree near Mackenzie, British Columbia, Canada (Fig. 1A) (27). Cellulolytic activities were significantly different among these four strains (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Streptomyces sp. DpondAA-B6 (SDPB6; NCBI Taxonomy ID 682311) was isolated from samples of D. ponderosae adults collected from naturally attacked P. contorta trees near Mackenzie, British Columbia, Canada (27). Adult insects were surface sterilized in 95% ethanol for 1 min, rinsed twice in sterile phosphate-buffered solution (PBS), and homogenized in PBS, and dilutions were spread onto agar plates supplemented with chitin.…”
Section: Methodsmentioning
confidence: 99%